An Efficient Curvature-Based Synthesis Methodology for Rotationally Symmetric Shaped Reflector Antennas - Manushanker Balasubramanian; Douglas H. Werner (IEEE Open Journal of Antennas and Propagation)
A previously proposed B-spline curvature-based synthesis technique is extended and applied to the design of rotationally symmetric reflector antennas with shaped beam patterns. The approach is based on representing a reflector as a single curve that can be modified to alter the reflector’s shape. The curvature is evaluated and represented using B-spline polynomials. First, the control points of the spline curve are defined as variables and then a new curvature profile is generated. Following this step, the corresponding curve is synthesized using the proposed iterative algorithm. This process of optimizing the curvature using B-spline polynomials offers the ability to better control the shape of a reflector with very few design variables. Furthermore, it significantly accelerates the convergence of the optimizer, making the approach very attractive compared to existing methods. The accuracy and validity of the proposed method are verified by multiple single and dual reflector antenna examples.